2016
DOI: 10.1530/ec-16-0029
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral inferior petrosal sinus sampling

Abstract: Simultaneous bilateral inferior petrosal sinus sampling (BIPSS) plays a crucial role in the diagnostic work-up of Cushing’s syndrome. It is the most accurate procedure in the differential diagnosis of hypercortisolism of pituitary or ectopic origin, as compared with clinical, biochemical and imaging analyses, with a sensitivity and specificity of 88–100% and 67–100%, respectively. In the setting of hypercortisolemia, ACTH levels obtained from venous drainage of the pituitary are expected to be higher than the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
76
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(85 citation statements)
references
References 129 publications
3
76
0
6
Order By: Relevance
“…Thus, this invasive procedure appears to yield a better diagnostic accuracy than MRI and dynamic testing used for the differential diagnosis of ACTH-dependent CS. Therefore it should be considered a useful diagnostic tool to confirm a pituitary source of ACTH overproduction, mainly in those patients with sustained hypercortisolism having a negative MRI and/or inconclusive biochemical evaluation (36,37,39,40,41,42,43). Although the ERCUSYN results, obtained in the largest series published to date, suggest that IPSS is extensively used across Europe, it was not reported in some countries, indicating that its use should be further implemented, for instance, by supporting technical skills training and procedure supplies acquisition.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this invasive procedure appears to yield a better diagnostic accuracy than MRI and dynamic testing used for the differential diagnosis of ACTH-dependent CS. Therefore it should be considered a useful diagnostic tool to confirm a pituitary source of ACTH overproduction, mainly in those patients with sustained hypercortisolism having a negative MRI and/or inconclusive biochemical evaluation (36,37,39,40,41,42,43). Although the ERCUSYN results, obtained in the largest series published to date, suggest that IPSS is extensively used across Europe, it was not reported in some countries, indicating that its use should be further implemented, for instance, by supporting technical skills training and procedure supplies acquisition.…”
Section: Discussionmentioning
confidence: 99%
“…Having excluded 22 lesions that were either centrally located or bilateral, the percentage of predictive lateralisation increased to 70% [74]. In contrast to this result, four other analyses of smaller groups [30,69,75,76]: 41, 27, 11, and 17 children, stated that ACTH sampling gives a better prediction of the site of the microadenoma than that by pituitary MR imaging. The first one [30] showed that BSIPSS correctly predicted the tumour position in all (4) cases; in the second [75] and third [76] research there was concordance between the BSIPSS finding and the position of the microadenoma at surgery in, respectively, 81% (17/21) and 91% (10/11) patients.…”
Section: Reviewmentioning
confidence: 83%
“…Bilateral simultaneous inferior petrosal sinus sampling is routinely performed in adult practice when the MRI does not show unequivocally a pituitary adenoma [30]. Bilateral simultaneous inferior petrosal sinus sampling is a highly specialised technique and should be performed by experienced interventional neuroradiologists with a team of trained operators [30,69]. In the majority of cases, general anaesthesia (GA) is not required; however, in young children GA may be necessary [30,70].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The localization was suggested when the inter-sinus gradient was > 1. 4. The results obtained were compared with the post operatory results: compatible histology and positive immunohistochemistry to adrenocorticotrophic hormone and/or the presence of criteria of cure.…”
Section: Introductionmentioning
confidence: 99%